Validating efficacy of Sericocomopsis hildebrandtii, Carissa edulis, and Ximenia americana in treating Taenia solium cysticercosis in pigs: A randomized controlled trial. (22nd November 2021) - Michaelis, Martin; Kabululu, Mwemezi L.; Boa, Mathias E.
Abstract: Ethnoveterinary use of plants dates back to ancient times. This study aimed to validate purported efficacy of Sericocomopsis hildebrandtii and a concoction of Carissa edulis and Ximenia americana in treating Taenia solium cysticercosis in pigs. Twenty-four infected pigs were randomly allocated to T1, T2, and T0 groups, each with eight pigs. Each T1 pig was provided with 8 g of S. hildebrandtii root powder, whereas each T2 pig was given 8 g of the concoction. T0 was a control. The pigs were slaughtered 16 weeks post treatment and carcase dissections were performed to establish cyst numbers. T1 cyst numbers were significantly lower than those of T0 ( p = .004) and T2 ( p = .013). No difference was observed between T2 and T0. This study validated efficacy of S. hildebrandtii but not of X. americana and C. edulis. Further studies are necessary for validation and documentation of plants of ethnoveterinary importance.